Management of acute chest syndrome in patients with sickle cell disease: a systematic review of randomized clinical trials. Issue 6 (3rd June 2022) - Niazi, Muhammad Rafay Khan; Chukkalore, Divya; Jahangir, Abdullah; Sahra, Syeda; Macdougall, Kira; Rehan, Maryam; Odaimi, Marcel
ABSTRACT: Introduction: Acute chest syndrome (ACS) accounts for the highest mortality in Sickle cell disease patients. Early diagnosis and timely management of ACS results in better outcomes. However, the effectiveness of most treatment modalities for ACS management has not been established. Areas Covered: To review the treatment modalities management protocols and highlight the effectiveness of each option a literature search was done. Randomized controlled trials that assessed the efficacy of different treatment modalities in ACS management in SCD patients were chosen and reviewed. Expert opinion: 11 randomized controlled trials were found that evaluated the efficacy of incentive spirometry, positive expiratory pressure device, intravenous dexamethasone, oral vs. intravenous morphine, inhaled nitric oxide, unfractionated heparin, and blood transfusion in the prevention or treatment of ACS. Although there are guidelines for ACS treatment, the available evidence is very limited to delineating the effectiveness of various interventions in ACS management. More high-quality studies and trials with a larger patient population can benefit this area to support the recommendations with stronger evidence.